Retakaful – An Integrated Mechanism to Enhance Prudence, Cost Effectiveness and Efficiency - Wan Ismail, Wan Zamri; Mohamed Yusof, Mohd Faiz; Ahmad, Ismail (Journal of Technology Management and Business, 2021)
The objective of this study is to highlight the current practice of retakaful and to explore means to enhance prudence, cost effectiveness and efficiency in managing retakaful which represents a major cost to the Participant Risk Fund (PRF). This is a qualitative study which discusses the theoretical and practical aspects of retakaful through literature review from published sources; articulated from the practitioner’s perspective. This study explains the concept and importance of retakaful, outlines the methods of retakaful, discusses the theory of efficiency, and analyses the cost of retakaful and its impact on the takaful business. This study highlights the best practices for prudent management of retakaful and outlines the methodologies for measuring the efficiency of retakaful. This study contributes to the current dearth of literature and research on takaful and retakaful as a nascent industry, compared to the more matured insurance and reinsurance industry. Hence, the conventional insurance and reinsurance theory and practice are also referred to as a benchmark. The study would provide better insight for the takaful industry on the mechanism to improve the management of retakaful as a critical component of the Enterprise Risk Management (ERM) of a takaful operation. Better management of retakaful will assist in bolstering the financial position of the PRF as a whole.